Post-Flood Recovery and Development of Administration and Public Services in Pidie Jaya - Zuliaden Jayus; Ismayli; Usman Boini (STMIK Indonesia Banda Aceh, 2026)
Floods are a natural disaster that significantly impacts the sustainability of government administration and the quality of public services in affected areas. Pidie Jaya Regency, as one of the areas vulnerable to flooding, faces serious challenges in maintaining the effectiveness of public administration functions after a disaster. This study aims to analyze the recovery process and strategies for developing public administration and services after the flood in Pidie Jaya Regency from a public administration perspective. The study focuses on institutional capacity, service governance, inter-agency coordination, and the role of community participation in the recovery phase. The research method used is a descriptive qualitative approach with data collection through interviews, observations, and documentation studies. The results show that post-flood public administration recovery requires institutional strengthening, service digitization, and adaptive policies based on disaster risk. The development of responsive and inclusive public services is key to increasing public trust and the resilience of local government institutions.